IMPRENSA, HISTÓRIA E IMAGENS: QUESTÕES SOBRE A COBERTURA DAS GUERRAS DA CORÉIA (1950-1953) E DO VIETNÃ (1964-1973) (Revista de História Regional, 2007)
The objective of this article is to discuss the construction of media about aspects of the coverage of the wars in Korea (1950-53) and Vietnam in the so called American Phase (1964-73). It states that actually there are two wars: the first one representing the real one with casualties and violence, within military schemes, dangerous situations for both sides in the so called operational theater and the second is the one represented by the media, to be followed by the people. In other words, the first war builds the second war and the second war builds the first war, in a double way relationship. The new technologies make the second war more complex as its representation draws it as near as possible to the first war and the effects on the public become more intense. Thepresence of the television has also interfered in the war representations.